Tourism development and sustainability in French Cerdagne - Philippe Bachimon; Pierre Dérioz; Mihaela Marc (Revue de Géographie Alpine)
The combined effect of problems related toclimate warming and the recent crisis in real estate has underlined the fragility of tourism in the Cerdagne region of southern France. Although the question of the very survival of tourism here can no longer be ignored, the possibility of its diversification, or even its restructuring, seems to be facing serious difficulties in becoming part of a public debate that is barely off the ground.